Hydrogenation catalyst, method for preparing and using the same, and method for hydrodenitrogenation
Patent Information
- Application Number
- CN202210813950.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-12
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2042-07-12
AI Technical Summary
[0005]本发明的目的是为了克服现有技术中加氢催化剂活性低和稳定性差的问题,提供一种加氢催化剂及其制备方法与应用、加氢脱氮的方法,该催化剂具有活性高和稳定性强的优点,尤其适用于馏分油中二次加工柴油含量高(20-70重量%)的馏分油,能够很好地去除馏分油中的氮,满足劣质柴油加工的需求
[0020] The catalyst provided by this invention contains at least two CO2 release peaks during programmed temperature oxidation. The catalyst has high activity and stability, and is especially suitable for treating distillate oils with a secondary diesel content of 20-70% by weight. It also exhibits excellent denitrification performance.
Smart Images

Figure CN117427648B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of hydrogenation catalysts, specifically to a hydrogenation catalyst, its method and application, and a method for hydrogenation denitrification. Background Technology
[0002] To improve refinery economics, the efficient utilization of low-grade diesel fuel has attracted widespread attention. Low-grade diesel fuel is rich in aromatics and can be converted into high-value gasoline or light aromatics. In the processing of low-grade diesel fuel, it is generally necessary to remove nitrogen oxides through a hydrorefining unit to facilitate subsequent cracking processes. The hydrorefining unit catalyst should possess high hydronitrogen removal activity and stability. Currently, the denitrogenation activity and stability of hydrorefining catalysts are insufficient and need further improvement to meet the requirements of low energy consumption and long cycle times.
[0003] Patent application No. 202011116861.8 discloses a method for preparing a hydrorefining catalyst for heavy diesel fractions. The method first prepares a filter cake containing Ni, Al, and W through a gelation reaction. Then, the filter cake and a Ni / Al mixture are mixed to obtain a solid-liquid mixture, which is then added in parallel with a sodium molybdate solution and a precipitant to a reaction vessel for a gelation reaction. After aging, the mixture undergoes solid-liquid separation, drying, and molding. The molded material is then desalted, washed, dried, and calcined to obtain the hydrorefining catalyst. Patent application No. 202010395989.6 discloses a hydrorefining catalyst and its preparation method and application. This catalyst comprises 50-80 wt% of a support and 20-50 wt% of an active metal component; wherein the support is an Al2O3-containing composite oxide. Patent application No. 201910297435.X discloses a hydrorefining catalyst, comprising a total content of 40-85% transition metal phosphides, 5-35% alumina, 2-18% magnesium (calculated as magnesium oxide), and 1-16% zirconium (calculated as zirconium oxide). Patent application No. 201810965384.9 discloses a diesel hydrodenitrification catalyst, using a support comprising γ-Al₂O₃, ZrO₂, and La₂O₃. The support is a hierarchical porous composite support prepared using polyamide-amine dendritic polymer as a pore-forming agent, and the active components are loaded onto the support through one or more impregnations. Patent application No. 201811455219.5 discloses a method for preparing a supported hydrogenation catalyst. The catalyst is prepared by contacting a γ-Al2O3 support with a solution containing the active metal-directed loading agent using one or more of the group consisting of sodium ethylenediaminetetramethylene phosphate, tetrabutylammonium fluoride and tartaric acid as active metal-directed loading agents.
[0004] As can be seen from the above, the existing methods for preparing hydrogenation catalysts and the composition of the catalysts are relatively complex, with low catalyst activity and poor stability. Their convenience and economy need to be improved. Summary of the Invention
[0005] The purpose of this invention is to overcome the problems of low activity and poor stability of hydrogenation catalysts in the prior art, and to provide a hydrogenation catalyst, its preparation method and application, and a method for hydrogenation denitrification. This catalyst has the advantages of high activity and strong stability, and is especially suitable for distillate oils with a high secondary diesel content (20-70% by weight). It can effectively remove nitrogen from distillate oils and meet the needs of processing inferior diesel.
[0006] To achieve the above objectives, the first aspect of the present invention provides a hydrogenation catalyst, wherein the catalyst comprises at least one Group VIB metal element, a co-active component, a phosphorus element, a support, and at least two of an organic alcohol compound, a carboxylic acid compound, and an organic amine compound;
[0007] The active component includes nickel and at least one of the optional elements of iron, ruthenium, and osmium;
[0008] Wherein, the proportion of the catalyst with a pore size distribution of 100-300 nm to the pore volume of the catalyst does not exceed 20%;
[0009] The catalyst contains at least two CO2 release peaks during the programmed temperature oxidation process. The temperature of the first release peak is between 210-280℃, and the temperature of the second release peak is between 320-380℃. The peak height ratio ranges from 0.5 to 4:1.
[0010] Preferably, the atomic ratio of nickel to the active component is not less than 0.8, and more preferably 0.85-1.
[0011] Preferably, the temperature of the first release peak is 230-260℃, the temperature of the second release peak is 320-360℃, and the ratio of peak height to peak height is 0.7-3.5:1.
[0012] Preferably, the pore size distribution of the catalyst in the range of 100-300 nm accounts for 5-20% of the catalyst pore volume.
[0013] Preferably, the molar ratio of the organic alcohol compound to the group VIB metal element is 0.2-4:1.
[0014] Preferably, the molar ratio of the carboxylic acid compound and / or organic amine compound to the co-active component is 0.3-1.5:1.
[0015] A second aspect of the present invention provides a method for preparing the hydrogenation catalyst described in the first aspect, the method comprising:
[0016] An impregnation method is used to introduce at least two compounds from the following groups into a carrier: a precursor of an active component, a Group VIB metal precursor, a phosphorus-containing compound, an organic alcohol compound, a carboxylic acid compound, and an organic amine compound, followed by drying.
[0017] The third aspect of this invention provides the application of the hydrogenation catalyst described in the first aspect in the hydrorefining of distillate oils.
[0018] A fourth aspect of the present invention provides a method for hydrodenitrification, wherein the method includes contacting the hydrodenitrification catalyst described in the first aspect with the distillate oil to be treated.
[0019] Preferably, the proportion of secondary processed diesel in the distillate oil to be treated is 20-70% by weight.
[0020] The catalyst provided by this invention contains at least two CO2 release peaks during programmed temperature oxidation. The catalyst has high activity and stability, and is especially suitable for treating distillate oils with a secondary diesel content of 20-70% by weight. It also exhibits excellent denitrification performance.
[0021] The inventors of this invention discovered in their research that using nickel and phosphorus elements in combination with two or more different types of organic compounds can significantly improve the activity of the hydrogenation catalyst. At the same time, introducing some phosphorus elements into the support can improve the dispersion of the active metal components and significantly improve the activity of the catalyst. Furthermore, in this invention, the proportion of the pore size distribution of the hydrogenation catalyst in the 100-300 nm range to the pore volume of the catalyst does not exceed 20%, which is more conducive to improving the activity and stability of the hydrogenation catalyst. Attached Figure Description
[0022] Figure 1 This is the CO2 release spectrum of the catalyst in Example 1. Detailed Implementation
[0023] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0024] In this invention, it is understood that "optionally" means that it may or may not be included.
[0025] The first aspect of the present invention provides a hydrogenation catalyst, wherein the catalyst comprises at least one Group VIB metal element, a co-active component, a phosphorus element, a support, and at least two of an organic alcohol compound, a carboxylic acid compound, and an organic amine compound;
[0026] The active component includes nickel and at least one of the optional elements of iron, ruthenium, and osmium;
[0027] Wherein, the proportion of the catalyst with a pore size distribution of 100-300 nm to the pore volume of the catalyst does not exceed 20%;
[0028] The catalyst contains at least two CO2 release peaks during the programmed temperature oxidation process. The temperature of the first release peak is between 210-280℃, and the temperature of the second release peak is between 320-380℃. The ratio of the peak heights is between 0.5 and 4:1.
[0029] In this invention, the first release peak temperature of 210-280℃ refers to a specific temperature value in which the peak value of the first release peak appears between 210-280℃, and the second release peak temperature of 320-380℃ refers to a specific temperature value in which the peak value of the second release peak appears between 320-380℃.
[0030] In this invention, it is understood that the CO2 emission peak temperature has an error of ±2℃.
[0031] In this invention, "peak height ratio" refers to the ratio of the peak height of the first release peak to the peak height of the second release peak, that is, peak height ratio = peak height of the first release peak / peak height of the second release peak.
[0032] In this invention, the CO2 emission peaks were analyzed on a NETZSCH STA 409PC / PG instrument. The catalyst to be tested was heated in an air atmosphere (heating rate of 10℃ / min), and the gas outlet of the instrument was monitored by a mass spectrometer to obtain the curve of CO2 produced by catalyst decomposition as a function of temperature.
[0033] This invention provides a hydrogenation catalyst with the specific structure and composition described above. By introducing two or more different types of organic compounds, the activity of the catalyst is significantly improved. This catalyst is particularly suitable for distillate oils in which the proportion of secondary processed diesel is 20-70% by weight. The catalyst has good activity and stability and can effectively remove nitrogen from the distillate oils in the process.
[0034] In this invention, preferably, based on the total weight of the catalyst and calculated as oxides, the content of the co-activating component is 1-15% by weight, more preferably 2-12% by weight, and even more preferably 3-8% by weight; the content of Group VIB metal elements is 12-50% by weight, and the content of Group VIB metal elements is 15-40% by weight, more preferably 20-35% by weight. The advantage of this preferred embodiment is that the catalyst has higher activity and stability.
[0035] In a preferred embodiment, the atomic ratio of nickel to the total amount of the co-active component is not less than 0.8, preferably 0.85-1. The advantage of this preferred embodiment is that it improves the denitrification performance of the catalyst.
[0036] In a preferred embodiment, the phosphorus content in the catalyst, calculated as P2O5, is 3-10% by weight, more preferably 3.5-9% by weight, and even more preferably 4-8% by weight. The advantage of this preferred embodiment is that the catalyst has higher activity.
[0037] In a preferred embodiment, the catalyst exhibits at least two CO2 release peaks during the temperature-programmed oxidation process, with the first peak temperature between 230-260°C and the second peak temperature between 320-360°C, and the peak height ratio ranging from 0.7 to 3.5:1. The advantage of this preferred embodiment is that the catalyst maintains higher activity and stability.
[0038] In a preferred embodiment, the pore size distribution of the catalyst in the 100-300 nm range accounts for 5-20% of the catalyst pore volume, more preferably 8-15%. The advantage of this preferred embodiment is that the larger pore size during the reaction promotes the diffusion of larger reactant molecules, reduces the formation of carbon deposits on the catalyst surface, and enhances catalyst stability.
[0039] In this invention, the selection range of Group VIB metal elements is relatively wide. Preferably, the Group VIB metal element is selected from at least one of chromium, molybdenum, and tungsten, and more preferably molybdenum.
[0040] In this invention, there are no specific limitations on the amount of the co-active component and the Group VIB metal element, as long as the performance of the hydrogenation catalyst is met. Preferably, the atomic ratio of the co-active component to the total amount of the co-active component and the Group VIB metal element is 0.1-0.5, more preferably 0.2-0.35. The advantage of this preferred embodiment is that the selection of the above-mentioned co-active component and the Group VIB metal element maintains a good synergistic effect to achieve higher catalytic performance.
[0041] In this invention, a wide range of carrier types can be selected, and conventional carriers in the art are all suitable for this invention. Preferably, the carrier is an alumina carrier.
[0042] In this invention, preferably, the phosphorus element in the catalyst comprises two parts: one part is introduced into the alumina support, and the other part is introduced during the preparation of the active metal component impregnation solution.
[0043] In a preferred embodiment, the alumina support contains phosphorus, hereinafter referred to as phosphorus-containing alumina. The advantage of this preferred embodiment is that the presence of a specific amount of phosphorus in the alumina support significantly promotes catalyst activity.
[0044] In a preferred embodiment, the phosphorus content in the alumina support, calculated as P2O5, accounts for 10-40% by weight of the total phosphorus content in the catalyst, preferably 20-30% by weight. The advantage of this preferred embodiment is that by rationally controlling the phosphorus content in the alumina support, the loading degree of the active metal component on the alumina support can be further improved, and the dispersion of the active metal component can be enhanced.
[0045] In this invention, phosphorus can be introduced into the formed alumina support, during the alumina support forming process, or during the preparation of the alumina support precursor. Preferably, it is introduced during the preparation of the alumina support precursor. When introduced during the preparation of the alumina precursor, phosphorus can be introduced by adding a phosphorus-containing compound during the preparation of the alumina precursor using the aluminum sulfate-sodium aluminate method. Specifically, phosphoric acid or phosphate can be introduced as a raw material or at any step in the preparation of the alumina precursor. By introducing phosphorus into the alumina precursor, the structural properties of the alumina support are improved, and the dispersion ability of the active metal components is promoted.
[0046] In this invention, the phosphorus element in the phosphorus-containing alumina support is provided by the alumina support precursor. In a preferred embodiment, the alumina support precursor is boehmite, and the boehmite contains phosphorus.
[0047] Generally, sodium-containing precursors are used in the preparation of boehmite, and such substances remain in the boehmite. In a preferred embodiment, the sodium oxide content in the boehmite does not exceed 0.08% by weight, preferably not more than 0.05% by weight. The advantage of this preferred embodiment is that it controls the sodium oxide content in the boehmite, further reduces the basicity centers, and thus gives the catalyst good activity, promoting the hydrodenitrification effect of the catalyst.
[0048] In this invention, there are no specific limitations on the preparation method of the phosphorus-containing alumina support; conventional preparation methods in the art are applicable to this invention. Preferably, the phosphorus-containing alumina support is prepared by extrusion molding; the specific operation method will not be described in detail here.
[0049] In this invention, to further improve the performance of the catalyst, a support with a specific composition and structure is selected as the support for the hydrogenation catalyst. Preferably, the alumina support has a water absorption rate greater than 0.9 mL / g, more preferably 0.95-1.3 mL / g, and a specific surface area greater than 260 m². 2 / g, further preferably 270-320m 2 / g, with an average pore size greater than 8nm, more preferably 10-15nm. The advantage of this preferred embodiment is that it provides a larger pore size to the support, promoting sufficient contact between the reactant molecules and the active component, thereby improving the denitrification activity and stability of the catalyst.
[0050] In a preferred embodiment, the pore size distribution of the alumina support in the range of 100-300 nm accounts for 5-15% of the pore volume of the alumina support, and more preferably 7-13%.
[0051] Using the aforementioned carrier with specific composition and structure (preferably an alumina carrier) has the advantage of providing a wide reaction space, thereby promoting contact between the reactant molecules and the active center.
[0052] In this invention, the specific surface area, pore volume, pore diameter, and pore distribution of the carrier (preferably an alumina carrier) are determined by mercury intrusion porosimetry.
[0053] In a particularly preferred embodiment, the catalyst comprises an organic alcohol compound, a carboxylic acid compound, and / or an organic amine compound. An advantage of this preferred embodiment is that selecting two or more organic compounds can significantly improve the catalyst's activity.
[0054] In a particularly preferred embodiment, the molar ratio of the organic alcohol compound to the Group VIB metal element is 0.2-4:1, preferably 0.5-2.5:1, and more preferably 0.6-2.2:1; the molar ratio of the carboxylic acid compound and / or organic amine compound to the co-activating component is 0.3-1.5:1, preferably 0.4-1.2:1, and more preferably 0.5-1.1:1. The advantage of this preferred embodiment is that it maintains a high degree of metal dispersion in the catalyst, thereby improving the catalyst's activity and stability.
[0055] In this invention, the range of organic alcohol compounds selected is relatively broad, and conventional organic alcohol compounds in the art are all applicable to this invention. Preferably, the organic alcohol compound is selected from at least one of monohydric alcohols, dihydric alcohols, and polyhydric alcohols. More preferably, the organic alcohol compound is selected from at least one of methanol, ethanol, propanol, isopropanol, butanol, isobutanol, pentaethanol, heptanol, ethylene glycol, glycerol, butanetetrol, polyethylene glycol, polyglycerol, pentaerythritol, xylitol, sorbitol, and trimethylolethane, and even more preferably, at least one of butanol, glycerol, propanol, and ethylene glycol.
[0056] In this invention, there is no specific limitation on the types of carboxylic acid compounds. Preferably, the carboxylic acid compound is selected from at least one of formic acid, acetic acid, propionic acid, citric acid, octanoic acid, adipic acid, malonic acid, succinic acid, maleic acid, valeric acid, hexanoic acid, decanoic acid, benzoic acid, phenylacetic acid, phthalic acid, terephthalic acid, stearic acid, and tartaric acid, and more preferably at least one of formic acid, citric acid, and acetic acid.
[0057] In this invention, there is no specific limitation on the type of organic amine compound. Preferably, the organic amine compound is selected from at least one of ethylenediamine, ethylenediaminetetraacetic acid, ethanolamine, triethanolamine, and cyclohexanediaminetetraacetic acid, and more preferably triethanolamine and / or cyclohexanediaminetetraacetic acid.
[0058] In this invention, there is no specific limitation on the size of the catalyst. Preferably, the equivalent diameter of the catalyst is 0.5-1.8 mm, and more preferably 0.8-1.6 mm.
[0059] In this invention, there is no specific limitation on the shape of the catalyst; conventional catalyst shapes in the art are applicable to this invention. Preferably, the catalyst is cylindrical, cloverleaf, four-leaf clover, disc, honeycomb, or other irregular shapes, and more preferably butterfly-shaped.
[0060] A second aspect of the present invention provides a method for preparing a hydrogenation catalyst, the method comprising: introducing a co-active component precursor, a Group VIB metal precursor, a phosphorus-containing compound, and at least two compounds selected from organic alcohols, carboxylic acids, and organic amines into a support by impregnation, followed by drying.
[0061] In this invention, the types of active ingredients, Group VIB metals, organic alcohols, carboxylic acids and organic amines have been described in the first aspect and will not be repeated here.
[0062] In a preferred embodiment, the precursor of the co-active component is selected from its respective soluble salt or chloride.
[0063] In a preferred embodiment, the nickel precursor is selected from at least one of nickel nitrate, basic nickel carbonate, nickel acetate, and nickel propionate.
[0064] In a preferred embodiment, the iron precursor is selected from at least one of ferric nitrate, ferric chloride, and ferric acetate.
[0065] In a preferred embodiment, the ruthenium precursor is selected from at least one of ruthenium nitrate, ruthenium chloride, and ruthenium acetate.
[0066] In a preferred embodiment, the osmium precursor is selected from osmium nitrate and / or osmium trichloride.
[0067] In a preferred embodiment, the Group VIB metal precursor is selected from at least one of ammonium heptamolybdate, ammonium molybdate, ammonium phosphomolybdate, ammonium metatungstate, and ethyl metatungstate.
[0068] In a preferred embodiment, the phosphorus-containing compound is selected from at least one of phosphoric acid, hypophosphoric acid, ammonium phosphate, and ammonium dihydrogen phosphate.
[0069] According to the present invention, there is no specific limitation on the impregnation method, and conventional impregnation methods in the art are applicable to the present invention. For example, it can be one of co-impregnation, stepwise impregnation, saturated impregnation, and supersaturated impregnation. In a preferred embodiment, the present invention uses co-impregnation to prepare the hydrogenation catalyst. In a more preferred embodiment, the impregnation method includes: impregnating the support with an impregnation solution containing at least two of the following: a co-active component precursor, a Group VIB metal precursor, a phosphorus-containing compound, and an organic alcohol compound, a carboxylic acid compound, and an organic amine compound.
[0070] In this invention, there is no specific limitation on the order of adding the co-active component precursor, the Group VIB metal precursor, the phosphorus-containing compound, and the organic alcohol compound, carboxylic acid compound, and organic amine compound, as long as it facilitates uniform mixing of all components. In a preferred embodiment, at least two of the organic alcohol compound, carboxylic acid compound, and organic amine compound (preferably an organic alcohol compound and a carboxylic acid compound and / or an organic amine compound), the co-active component precursor, and the Group VIB metal precursor are added to an aqueous solution of the phosphorus-containing compound to provide the impregnation solution. In this invention, the order of adding the organic alcohol compound, carboxylic acid compound and / or organic amine compound, phosphorus-containing compound, and metal precursor can also be interchanged.
[0071] In this invention, the hydrogenation catalyst can be prepared by the following method: First, a phosphorus-containing compound is dissolved in water to obtain a phosphorus-containing aqueous solution. Then, at least two of the following are added: an organic alcohol compound, a carboxylic acid compound, and an organic amine compound (preferably an organic alcohol compound, a carboxylic acid compound, and / or an organic amine compound), a Group VIB metal precursor, and a co-active component precursor. The mixture is heated and stirred until completely dissolved, and kept at a constant temperature to obtain an impregnation solution. The water absorption rate of the alumina support is measured, and the liquid absorption rate of the alumina support is calculated according to the formula: water absorption rate of alumina support - 0.1. According to the liquid absorption rate of the alumina support, the impregnation solution is adjusted to the corresponding volume (liquid absorption rate of alumina support × support mass). The impregnation solution is then mixed evenly with the corresponding mass of alumina support and allowed to stand. Finally, the mixture is dried to prepare the hydrogenation catalyst.
[0072] In this invention, there are no specific limitations on the stirring conditions. Preferably, the stirring temperature is 40-100℃ and the stirring time is 1-8 hours.
[0073] In this invention, there are no specific limitations on the selection of drying conditions. Preferably, the drying conditions include: a temperature of 60-200℃ and a time of 2-10 hours.
[0074] In a preferred embodiment, the present invention employs a non-calcination treatment. The advantage of this preferred embodiment is that it retains organic matter within the catalyst, promoting the formation of more active sites and maintaining the catalyst's high initial activity.
[0075] The third aspect of this invention provides the application of the hydrogenation catalyst described in the first aspect in the hydrorefining of distillate oils.
[0076] A fourth aspect of the present invention provides a method for hydrodenitrification, wherein the method includes contacting the hydrodenitrification catalyst described in the first aspect with the distillate oil to be treated.
[0077] In a particularly preferred embodiment, the proportion of secondary hydrotreated diesel in the distillate oil to be treated is 20-70% by weight. This preferred embodiment can better utilize the hydrodenitrification activity and stability of the catalyst, so that the nitrogen content in the product can meet the National VI clean diesel quality standard or the requirements for further processing.
[0078] In a preferred embodiment, the distillate oil to be treated contains 45-75% by weight straight-run diesel, 25-55% by weight catalytic diesel, and 50-2000 ppm nitrogen.
[0079] In this invention, the secondary hydrogenated diesel refers to catalytic diesel.
[0080] In a preferred embodiment, the catalyst needs to be converted from an oxidized state to a sulfidized state before use. In this invention, there is no specific limitation on the sulfidation method; conventional sulfidation methods in the art are applicable. Preferably, for example, it can be either dry sulfidation or wet sulfidation. There is no particular limitation on the type of sulfiding agent; it can be selected according to conventional methods in the art.
[0081] In this invention, preferably, the vulcanization conditions include: a heating rate of 5-60℃ / h, a vulcanization temperature of 280-420℃, a vulcanization time of 8-48h, a vulcanization pressure of 0.1-15MPa, and a volume hourly space velocity of 0.5-20h. -1 The hydrogen-to-oil volume ratio is 100-2000:1.
[0082] In this invention, preferably, the contact conditions include a temperature of 320-400℃, a reaction pressure of 6-20 MPa, and a volume hourly space velocity of 0.5-3 h⁻¹. -1 The hydrogen-to-oil volume ratio is 300-1500:1.
[0083] The following embodiments will further illustrate the present invention.
[0084] In the following examples, the hydrogenation performance of the catalyst was tested in a high-throughput hydrogenation reactor. First, the oxidized catalyst was converted to a sulfidized catalyst using a temperature-programmed sulfidation method. The sulfidation conditions were: sulfidation pressure of 6.4 MPa, kerosene containing 22% CS by weight as the sulfidation oil, and a volume hourly space velocity of 2 h⁻¹. -1 The hydrogen-to-oil ratio was 300 v / v. The mixture was first kept at 230℃ for 6 hours, then heated to 360℃ for 8 hours of sulfidation, with a heating rate of 10℃ / h for each stage. After sulfidation, the feedstock was switched for hydrodenitrification activity testing. The distillate oil to be treated contained 45% by weight straight-run diesel, 55% by weight catalytic diesel, and 951 ppm nitrogen. The test conditions were: pressure 6.4 MPa, volumetric hourly space velocity (VHSV) 1.3 h⁻¹. -1 The hydrogen-to-oil ratio was 600 v / v, and the reaction temperature was 360℃. The reaction proceeded stably for 12 days, and the nitrogen content in the products on day 1 and day 12 was analyzed. The stability of the catalyst was expressed by calculating the rate constant after the reaction stabilized and the initial rate constant; the ratio of the rate constant after stabilization to the initial rate constant is called the activity retention. The higher the activity retention, the better the catalyst stability.
[0085] The composition of the catalyst was calculated based on the feed amount. The pore distribution, pore size, and pore volume in the catalyst and support (100-300 nm) were determined using mercury porosimetry. The nitrogen mass fraction in the product was analyzed using a sulfur-nitrogen analyzer (Thermo Fisher Scientific TN / TS3000).
[0086] CO2 emission peaks were measured using a temperature-programmed oxidation method. Analysis was performed on a NETZSCH STA409 PC / PG instrument. The sample was heated in air (heating rate 10 °C / min), and the temperature was monitored at the instrument's gas outlet using a mass spectrometer to obtain a curve showing the change in CO2 production from sample decomposition with temperature.
[0087] The reaction rate constant is calculated using the following formula: k = LHSV × ln(N) f / N p LHSV is the reaction space velocity, N f N p These are the nitrogen contents of the raw materials and the products, respectively.
[0088] Example 1
[0089] A certain amount of MoO3, basic nickel carbonate, ethylene glycol, and citric acid were added to an aqueous solution containing phosphoric acid, and the solution was heated and stirred at 85°C for 3 hours until completely dissolved to obtain an impregnation solution containing the active metal. The impregnation solution was then mixed evenly with a support and allowed to stand for 3 hours. After drying at 120°C for 5 hours, a catalyst with a particle size of 1.6 mm and a butterfly shape was prepared. The pore size distribution of the catalyst in the 100-300 nm range accounted for 15% of the catalyst pore volume.
[0090] The catalyst was prepared using a γ-alumina support with a water absorption rate of 1.08 mL / g and a specific surface area of 280 m². 2 The alumina support has an average pore size of 14.8 nm, with pores ranging from 100 to 300 nm accounting for 12% of the total pore volume. The sodium oxide content in the support is 0.05% by weight. The alumina support used to prepare the catalyst contains phosphorus, which comes from the boehmite powder used in its preparation. The phosphorus-containing boehmite powder is obtained by introducing a certain amount of phosphoric acid during the boehmite powder preparation process. The phosphorus-containing boehmite powder is shaped and calcined at 600℃ for 3 hours to obtain the phosphorus-containing alumina support.
[0091] The catalyst contained 30.0 wt% MoO3, 4.5 wt% NiO, an atomic ratio of Ni / (Ni+Mo) of 0.22, and 7.0 wt% P2O5, of which 30 wt% of the P2O5 came from the support. The molar ratio of ethylene glycol to Group VIB metals was 1.5:1, and the molar ratio of citric acid to nickel was 1:1. The catalyst was tested using temperature-programmed oxidation. Figure 1 As shown, CO2 release peaks appeared at 238℃ and 345℃, respectively, and the ratio of their peak heights was 3.5.
[0092] After sulfidation and reaction testing, the nitrogen content in the product was 1.5 ppm. Under stable reaction conditions, the activity retention was 89.5% after 12 days of reaction.
[0093] Example 2
[0094] A certain amount of MoO3, basic nickel carbonate, glycerol, and acetic acid were added to an aqueous solution containing phosphoric acid, and the solution was heated and stirred at 85°C for 3 hours until completely dissolved to obtain an impregnation solution containing active metals. The impregnation solution was mixed evenly with a support and allowed to stand for 3 hours. After drying at 120°C for 5 hours, a catalyst with a particle size of 1.6 mm and a butterfly shape was prepared. The pore size distribution of the catalyst in the 100-300 nm range accounted for 15% of the catalyst pore volume.
[0095] Example 2 uses the same carrier as Example 1.
[0096] The catalyst contained 24.0 wt% MoO3, 7.0 wt% NiO, an atomic ratio of Ni / (Ni+Mo) of 0.36, and 6.5 wt% P2O5, of which 20 wt% of the P2O5 came from the support. The molar ratio of glycerol to Group VIB metal was 1.2:1, and the molar ratio of acetic acid to nickel was 1.5:1. The catalyst was tested using temperature-programmed oxidation, and CO2 release peaks appeared at 240℃ and 340℃, with a peak height ratio of 3.3.
[0097] After sulfidation and reaction testing, the nitrogen content in the product was 1.8 ppm. Under stable reaction conditions, the activity retention was 88.6% after 12 days of reaction.
[0098] Example 3
[0099] A certain amount of MoO3, basic nickel carbonate, butanol, and acetic acid were added to an aqueous solution containing phosphoric acid, and the solution was heated and stirred at 85°C for 3 hours until completely dissolved to obtain an impregnation solution containing active metals. The impregnation solution was then mixed evenly with a support and allowed to stand for 3 hours. After drying at 120°C for 5 hours, a catalyst with a particle size of 1.6 mm and a butterfly shape was prepared. The pore size distribution of the catalyst in the 100-300 nm range accounted for 15% of the catalyst pore volume.
[0100] Example 3 uses the same carrier as Example 1.
[0101] The catalyst contained 38.0 wt% MoO3, 6.5 wt% NiO, an atomic ratio of Ni / (Ni+Mo) of 0.25, and 5.0 wt% P2O5, of which 10 wt% of the P2O5 came from the support. The molar ratio of butanol to Group VIB metal was 0.6:1, and the molar ratio of citric acid to nickel was 1.2:1. The catalyst was tested using temperature-programmed oxidation, and CO2 release peaks appeared at 230℃ and 348℃, with a peak height ratio of 1.9.
[0102] After sulfidation and reaction testing, the nitrogen content in the product was 0.9 ppm. Under stable reaction conditions, the activity retention was 86.5% after 12 days of reaction.
[0103] Example 4
[0104] A certain amount of MoO3, basic nickel carbonate, butanol, and triethanolamine were added to an aqueous solution containing phosphoric acid, and the solution was heated and stirred at 85°C for 3 hours until completely dissolved to obtain an impregnation solution containing active metals. The impregnation solution was mixed evenly with a support and allowed to stand for 3 hours. After drying at 120°C for 5 hours, a catalyst with a particle size of 1.6 mm and a butterfly shape was prepared. The pore size distribution of the catalyst in the 100-300 nm range accounted for 15% of the catalyst pore volume.
[0105] Example 4 uses the same carrier as Example 1.
[0106] The catalyst contained 26.0 wt% MoO3, 5.5 wt% NiO, an atomic ratio of Ni / (Ni+Mo) of 0.29, and 4.5 wt% P2O5, of which 10 wt% of the P2O5 came from the support. The molar ratio of butanol to Group VIB metal was 1:1, and the molar ratio of triethanolamine to nickel was 1:1. The catalyst was tested using temperature-programmed oxidation, and CO2 release peaks appeared at 230℃ and 332℃, with a peak height ratio of 2.7.
[0107] After sulfidation and reaction testing, the nitrogen content in the product was 1.9 ppm. Under stable reaction conditions, the activity retention was 87.5% after 12 days of reaction.
[0108] Example 5
[0109] A certain amount of MoO3, basic nickel carbonate, ethylene glycol, and citric acid were added to an aqueous solution containing phosphoric acid, and the solution was heated and stirred at 95°C for 3 hours until completely dissolved to obtain an impregnation solution containing the active metal. The impregnation solution was then mixed evenly with a support and allowed to stand for 3 hours. After drying at 120°C for 5 hours, a catalyst with a particle size of 1.6 mm and a butterfly shape was prepared. The pore size distribution of the catalyst in the 100-300 nm range accounted for 10% of the catalyst pore volume.
[0110] The catalyst was prepared using a γ-alumina support with a water absorption rate of 1.04 mL / g and a specific surface area of 285 m². 2 / g, with an average pore size of 12.6nm, and the volume of pores with a size of 100-300nm accounting for 8% of the total pore volume. The sodium oxide content in the support is 0.03% by weight. The alumina support used to prepare the catalyst does not contain phosphorus.
[0111] The catalyst contained 26.0 wt% MoO3, 5.5 wt% NiO, an atomic ratio of Ni / (Ni+Mo) of 0.29, and 5.9 wt% P2O5. The molar ratio of ethylene glycol to Group VIB metals was 0.8:1, and the molar ratio of citric acid to nickel was 1:1. The catalyst was tested using temperature-programmed oxidation, and CO2 release peaks appeared at 240℃ and 345℃, with a peak height ratio of 1.2.
[0112] After sulfidation and reaction testing, the nitrogen content in the product was 2.1 ppm. Under stable reaction conditions, the activity retention was 85.3% after 12 days of reaction.
[0113] Example 6
[0114] A certain amount of MoO3, basic nickel carbonate, ferric acetate, ethylene glycol, and citric acid were added to an aqueous solution containing phosphoric acid. The solution was heated and stirred at 95°C for 3 hours until completely dissolved, obtaining an impregnation solution containing the active metal. The impregnation solution was mixed evenly with a support and allowed to stand for 3 hours. After drying at 120°C for 5 hours, a catalyst with a particle size of 1.6 mm and a butterfly shape was prepared. The pore size distribution of the catalyst in the 100-300 nm range accounted for 15% of the catalyst pore volume.
[0115] Example 6 uses the same carrier as Example 1.
[0116] The catalyst contained 26.0 wt% MoO3, 3.0 wt% NiO, and 2.4% FeO. The atomic ratio of (Ni+Fe) / (Ni+Fe+Mo) was 0.29, the atomic ratio of Ni / (Ni+Fe) was 0.55, and the P2O5 content was 5.9 wt%. The molar ratio of ethylene glycol to Group VIB metals was 0.8:1, and the molar ratio of citric acid to Group VIII elements was 1:1. The catalyst was tested using temperature-programmed oxidation, and CO2 release peaks appeared at 242℃ and 340℃, with a peak height ratio of 1.5.
[0117] After sulfidation and reaction testing, the nitrogen content in the product was 3.5 ppm. Under stable reaction conditions, the activity retention was 84.3% after 12 days of reaction.
[0118] Example 7
[0119] A certain amount of MoO3, basic nickel carbonate, ruthenium acetate, ethylene glycol, and citric acid were added to an aqueous solution containing phosphoric acid. The solution was heated and stirred at 90°C for 4 hours until completely dissolved, obtaining an impregnation solution containing the active metal. The impregnation solution was mixed evenly with a support and allowed to stand for 2 hours. After drying at 130°C for 5 hours, a catalyst with a particle size of 1.6 mm and a butterfly shape was prepared. The pore size distribution of the catalyst in the 100-300 nm range accounted for 15% of the catalyst pore volume.
[0120] Example 7 uses the same carrier as Example 1.
[0121] The catalyst contained 26.0 wt% MoO3, 5.5 wt% NiO, and 0.8% RuO2. The atomic ratio of (Ni+Ru) / (Ni+Ru+Mo) was 0.306, the atomic ratio of Ni / (Ni+Ru) was 0.925, and the P2O5 content was 7 wt%, of which 30 wt% of the P2O5 came from the support. The molar ratio of ethylene glycol to Group VIB metals was 1.5:1, and the molar ratio of citric acid to Group VIII elements was 0.8:1. The catalyst was tested using temperature-programmed oxidation, and CO2 release peaks appeared at 248℃ and 340℃, with a peak height ratio of 2.6.
[0122] After sulfidation and reaction testing, the nitrogen content in the product was 1.3 ppm. Under stable reaction conditions, the activity retention was 87.9% after 12 days of reaction.
[0123] Example 8
[0124] A certain amount of MoO3, basic nickel carbonate, glycerol, and citric acid were added to an aqueous solution containing phosphoric acid, and the solution was heated and stirred at 95°C for 3 hours until completely dissolved to obtain an impregnation solution containing active metals. The impregnation solution was mixed evenly with a support and allowed to stand for 2 hours. After drying at 130°C for 3 hours, a catalyst with a particle size of 1.6 mm and a butterfly shape was prepared. The pore size distribution of the catalyst in the 100-300 nm range accounted for 15% of the catalyst pore volume.
[0125] Example 8 uses the same carrier as Example 1.
[0126] The catalyst contained 22.0 wt% MoO3, 7.9 wt% NiO, an atomic ratio of Ni / (Ni+Mo) of 0.41, and 7.5 wt% P2O5, of which 20 wt% of the P2O5 came from the support. The molar ratio of glycerol to Group VIB metal was 1:1, and the molar ratio of citric acid to nickel was 0.8:1. The catalyst was tested using temperature-programmed oxidation, and CO2 release peaks appeared at 240℃ and 335℃, with a peak height ratio of 1.7.
[0127] After sulfidation and reaction testing, the nitrogen content in the product was 2.8 ppm. Under stable reaction conditions, the activity retention was 83.5% after 12 days of reaction.
[0128] Example 9
[0129] A certain amount of MoO3, basic nickel carbonate, ethylene glycol, and citric acid were added to an aqueous solution containing phosphoric acid, and the solution was heated and stirred at 85°C for 3 hours until completely dissolved to obtain an impregnation solution containing the active metal. The impregnation solution was then mixed evenly with a support and allowed to stand for 3 hours. After drying at 120°C for 5 hours, a catalyst with a particle size of 1.6 mm and a butterfly shape was prepared. The pore size distribution of the catalyst in the 100-300 nm range accounted for 15% of the catalyst pore volume.
[0130] Example 9 uses the same carrier as Example 1.
[0131] The catalyst contained 30.0 wt% MoO3, 4.5 wt% NiO, an atomic ratio of Ni / (Ni+Mo) of 0.22, and 7.0 wt% P2O5, of which 30 wt% of the P2O5 was derived from the support. The molar ratio of ethylene glycol to Group VIB metals was 0.3:1, and the molar ratio of citric acid to nickel was 1:1. The catalyst was tested using temperature-programmed oxidation, and CO2 release peaks appeared at 243℃ and 342℃, with a peak height ratio of 0.73.
[0132] After sulfidation and reaction testing, the nitrogen content in the product was 3.7 ppm. Under stable reaction conditions, the activity retention was 87.7% after 12 days of reaction.
[0133] Example 10
[0134] A certain amount of MoO3, basic nickel carbonate, ethylene glycol, and citric acid were added to an aqueous solution containing phosphoric acid, and the solution was heated and stirred at 85°C for 3 hours until completely dissolved to obtain an impregnation solution containing active metals. The impregnation solution was then mixed evenly with a support and allowed to stand for 3 hours. After drying at 120°C for 5 hours, a catalyst with a particle size of 1.6 mm and a butterfly shape was prepared. The pore size distribution of the catalyst in the 100-300 nm range accounted for 1.2% of the catalyst pore volume.
[0135] The catalyst was prepared using a γ-alumina support with a water absorption rate of 0.96 mL / g and a specific surface area of 285 m². 2The alumina support has an average pore size of 12.6 nm, with pores ranging from 100 to 300 nm accounting for 1% of the total pore volume. The sodium oxide content in the support is 0.05% by weight. The alumina support used to prepare the catalyst contains phosphorus, which comes from the boehmite powder used in its preparation. The phosphorus-containing boehmite powder is obtained by introducing a certain amount of phosphoric acid during the boehmite powder preparation process. The phosphorus-containing boehmite powder is shaped and calcined at 600℃ for 3 hours to obtain the phosphorus-containing alumina support.
[0136] The catalyst contained 30.0 wt% MoO3, 4.5 wt% NiO, an atomic ratio of Ni / (Ni+Mo) of 0.22, and 7.0 wt% P2O5, of which 30 wt% of the P2O5 came from the support. The molar ratio of ethylene glycol to Group VIB metals was 1.0:1, and the molar ratio of citric acid to nickel was 0.8:1. The catalyst was tested using temperature-programmed oxidation, and CO2 release peaks appeared at 248℃ and 343℃, with a peak height ratio of 2.4.
[0137] After sulfidation and reaction testing, the nitrogen content in the product was 3.2 ppm. Under stable reaction conditions, the activity retention was 84.8% after 12 days of reaction.
[0138] Comparative Example 1
[0139] A certain amount of MoO3, basic nickel carbonate, and citric acid were added to an aqueous solution containing phosphoric acid, and the solution was heated and stirred at 95°C for 2 hours until completely dissolved to obtain an impregnation solution containing the active metal. The impregnation solution was then mixed evenly with a support and allowed to stand for 3 hours. After drying at 120°C for 5 hours, a catalyst with a particle size of 1.6 mm and a butterfly shape was prepared. The pore size distribution of the catalyst in the 100-300 nm range accounted for 15% of the catalyst pore volume.
[0140] Comparative Example 1 uses the same carrier as in Example 1.
[0141] The catalyst contained 30.0 wt% MoO3, 4.5 wt% NiO, an atomic ratio of Ni / (Ni+Mo) of 0.22, and 7.0 wt% P2O5, of which 30 wt% of the P2O5 came from the support. The molar ratio of citric acid to nickel was 0.8:1. The catalyst was tested using temperature-programmed oxidation, and a CO2 release peak appeared at 360℃.
[0142] After sulfidation and reaction testing, the nitrogen content in the product was 7.9 ppm. Under stable reaction conditions, the activity retention was 81.0% after 12 days of reaction.
[0143] Comparative Example 2
[0144] A certain amount of MoO3, basic nickel carbonate, and glycerol were added to an aqueous solution containing phosphoric acid, and the solution was heated and stirred at 95°C for 2 hours until completely dissolved to obtain an impregnation solution containing active metals. The impregnation solution was mixed evenly with a support and allowed to stand for 3 hours. After drying at 120°C for 5 hours, a catalyst with a particle size of 1.6 mm and a butterfly shape was prepared. The pore size distribution of the catalyst in the 100-300 nm range accounted for 15% of the catalyst pore volume.
[0145] Comparative Example 2 uses the same carrier as in Example 1.
[0146] The catalyst contained 24.0 wt% MoO3, 7 wt% NiO, an atomic ratio of Ni / (Ni+Mo) of 0.36, and 6.5 wt% P2O5, of which 20 wt% of the P2O5 came from the support. The molar ratio of glycerol to nickel was 1.2:1.
[0147] The catalyst was tested using temperature-programmed oxidation, and a CO2 release peak appeared at 235℃.
[0148] After sulfidation and reaction testing, the nitrogen content in the product was 10.2 ppm. Under stable reaction conditions, the activity retention was 78.5% after 12 days of reaction.
[0149] Comparative Example 3
[0150] A certain amount of MoO3, basic nickel carbonate, and citric acid were added to an aqueous solution containing phosphoric acid, and the solution was heated and stirred at 95°C for 2 hours until completely dissolved to obtain an impregnation solution containing active metals. The impregnation solution was then mixed evenly with a support and allowed to stand for 3 hours. After drying at 120°C for 5 hours, a catalyst with a particle size of 1.6 mm and a butterfly shape was prepared. The pore size distribution of the catalyst in the 100-300 nm range accounted for 30% of the catalyst pore volume.
[0151] The carrier used in Comparative Example 3 was prepared using the same process as the carrier in Example 1. The carrier was γ-alumina, with a water absorption rate of 1.3 mL / g and a specific surface area of 270 m². 2 / g, with an average pore size of 16.5nm, and pores with a size of 100-300nm accounting for 25% of the total pore volume. The sodium oxide content in the support is 0.05% by weight.
[0152] The catalyst contained 30.0 wt% MoO3, 4.5 wt% NiO, an atomic ratio of Ni / (Ni+Mo) of 0.22, and 7.0 wt% P2O5, of which 30 wt% of the P2O5 came from the support. The molar ratio of citric acid to nickel was 0.8:1. The catalyst was tested using temperature-programmed oxidation, and a CO2 release peak appeared at 365℃.
[0153] After sulfidation and reaction testing, the nitrogen content in the product was 9.2 ppm. Under stable reaction conditions, the activity retention was 79.7% after 12 days of reaction.
[0154] As can be seen from the examples and comparative examples, the present invention has good inventive effects, and the prepared catalyst has high hydrodenitrification activity and stability, and has good prospects for industrial application.
[0155] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A method for hydrodenitrification, characterized in that, The method involves contacting the hydrogenation catalyst with the distillate oil to be treated; The hydrogenation catalyst comprises at least one Group VIB metal element, a co-active component, phosphorus element, a support, and organic alcohol compounds, carboxylic acid compounds, or organic amine compounds; The active component includes nickel and at least one of the optional elements of iron, ruthenium, and osmium; Wherein, the proportion of the catalyst with a pore size distribution of 100-300 nm to the pore volume of the catalyst does not exceed 20%; The catalyst contains at least two CO2 release peaks during the programmed temperature oxidation process, with the first release peak temperature at 210-280℃ and the second release peak temperature at 320-380℃, and the peak height ratio ranges from 0.5 to 4:
1. Among them, the atomic ratio of nickel to the total amount of the active components is not less than 0.8; The carrier is an alumina carrier; the alumina carrier contains phosphorus. Of which, based on P2O5, phosphorus in the alumina support accounts for 10-40% by weight of the total phosphorus content in the catalyst; Wherein, the molar ratio of the organic alcohol compound to the group VIB metal element is 0.2-4:1, and the molar ratio of the carboxylic acid compound or organic amine compound to the co-active component is 0.3-1.5:1; Among them, the distillate oil to be treated contains 45-75% by weight of straight-run diesel, 25-55% by weight of catalytic diesel, and 50-2000 ppm of nitrogen.
2. The method according to claim 1, wherein, Based on the total weight of the catalyst, the content of the co-activating component, calculated as oxide, is 1-15% by weight, and the content of Group VIB metal elements is 12-50% by weight.
3. The method according to claim 1, wherein, The atomic ratio of nickel to the total amount of the active component is 0.85-1.
4. The method according to claim 1, wherein, The phosphorus content in the catalyst is 3-10% by weight, calculated as P2O5.
5. The method according to claim 1, wherein, The catalyst contains at least two CO2 release peaks during the programmed temperature oxidation process. The temperature of the first release peak is between 230-260℃, and the temperature of the second release peak is between 320-360℃. The peak height ratio ranges from 0.7 to 3.5:
1.
6. The method according to claim 1, wherein, The catalyst has a pore size distribution of 100-300 nm accounting for 5-20% of the catalyst pore volume.
7. The method according to any one of claims 1-6, wherein, The group VIB metal element is selected from at least one of chromium, molybdenum, and tungsten.
8. The method according to any one of claims 1-6, wherein, The atomic ratio of the co-active component to the total amount of the co-active component and the Group VIB metal elements is 0.1-0.
5.
9. The method according to claim 8, wherein, The atomic ratio of the co-active component to the total amount of the co-active component and Group VIB metal elements is 0.2-0.
35.
10. The method according to claim 1, wherein, Based on P2O5, phosphorus in the alumina support accounts for 20-30% of the total phosphorus content in the catalyst.
11. The method according to claim 1, wherein, The precursor of the alumina carrier is boehmite, which contains phosphorus.
12. The method according to claim 11, wherein, The sodium oxide content in the pseudoboehmite does not exceed 0.08% by weight.
13. The method according to claim 12, wherein, The sodium oxide content in the pseudoboehmite does not exceed 0.05% by weight.
14. The method according to claim 1, wherein, The alumina carrier has a water absorption rate greater than 0.9 mL / g and a specific surface area greater than 260 m². 2 / g, with an average pore size greater than 8nm.
15. The method according to claim 1, wherein, The pore size distribution of the alumina support in the 100-300 nm range accounts for 5-15% of the pore volume of the alumina support.
16. The method according to claim 1, wherein, The organic alcohol compound is selected from at least one of methanol, ethanol, propanol, isopropanol, butanol, isobutanol, pentanol, heptanol, ethylene glycol, glycerol, butanetetraethanolamine, polyethylene glycol, polyglycerol, pentaerythritol, xylitol, sorbitol and trimethylolethane.
17. The method according to claim 16, wherein, The organic alcohol compound is selected from at least one of butanol, glycerol, propanol, and ethylene glycol.
18. The method according to claim 1, wherein, The carboxylic acid compound is selected from at least one of formic acid, acetic acid, propionic acid, citric acid, octanoic acid, adipic acid, malonic acid, succinic acid, maleic acid, valeric acid, hexanoic acid, decanoic acid, benzoic acid, phenylacetic acid, phthalic acid, terephthalic acid, stearic acid, and tartaric acid.
19. The method according to claim 18, wherein, The carboxylic acid compound is selected from at least one of formic acid, citric acid, and acetic acid.
20. The method according to claim 1, wherein, The organic amine compound is selected from at least one of ethylenediamine, ethylenediaminetetraacetic acid, ethanolamine, triethanolamine, and cyclohexanediaminetetraacetic acid.
21. The method according to any one of claims 1-6, wherein, The equivalent diameter of the catalyst is 0.5-1.8 mm.
22. The method according to claim 21, wherein, The equivalent diameter of the catalyst is 0.8-1.6 mm.
23. The method according to any one of claims 1-6, wherein, The catalyst may be cylindrical, clover-shaped, four-leaf clover-shaped, butterfly-shaped, honeycomb-shaped, or other irregular shapes.
24. The method according to any one of claims 1-6, wherein, The preparation method of the hydrogenation catalyst includes: An impregnation method is used to introduce at least two of the following into a carrier: a precursor of an active component, a Group VIB metal precursor, a phosphorus-containing compound, and an organic alcohol, carboxylic acid, or organic amine compound, followed by drying.
25. The method according to claim 24, wherein, The impregnation method includes impregnating the carrier with an impregnation solution containing a precursor of an active component, a Group VIB metal precursor, a phosphorus-containing compound, and an organic alcohol compound, a carboxylic acid compound, or an organic amine compound.
26. The method of claim 25, wherein, The organic alcohol compound, carboxylic acid compound or organic amine compound, precursor of the active component, and group VIB metal precursor are respectively added to an aqueous solution containing a phosphorus compound to provide the impregnation solution.
27. The method according to claim 24, wherein, The drying conditions include a temperature of 60-200℃ and a time of 2-10 hours.
28. The method according to claim 1, wherein, The proportion of secondary processed diesel in the distillate oil to be processed is 20-70% by weight.
29. The method according to claim 1, wherein, Contact conditions include a temperature of 320-400℃, a pressure of 6-20 MPa, and a volumetric hourly space velocity of 0.5-3 h⁻¹. -1 The hydrogen-to-oil volume ratio is 300-1500:1.
Citation Information
Patent Citations
A diesel hydrodenitrogenation catalyst and a preparing method and application thereof
CN108993521A
Supported hydrogenation catalyst and preparation method thereof
CN111250103A
Hydrofining catalyst, and preparation method and application thereof
CN111558377A
Hydrofining catalyst and preparation method thereof
CN111822017A
A method for preparing a catalyst for the hydrorefining of heavy diesel fractions
CN114433117B